2012
DOI: 10.1016/j.jhep.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal decontamination inhibits TLR4 dependent fibronectin-mediated cross-talk between stellate cells and endothelial cells in liver fibrosis in mice

Abstract: Background/Aims Liver fibrosis is associated with angiogenesis and leads to portal hypertension. Certain antibiotics reduce complications of liver failure in humans, however, effect of antibiotics on the pathologic alterations of the disease are not fully understood. The aim of this study was to test whether the non-absorbable antibiotic rifaximin could attenuate fibrosis progression and portal hypertension in vivo, and explore potential mechanisms in vitro. Methods Effect of rifaximin on portal pressure, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 41 publications
5
96
1
4
Order By: Relevance
“…We hypothesized that adhesion between exosomes and HSC may require ligand/receptor interactions to facilitate chemotactic signaling. FN is a glycoprotein of the extracellular matrix that is secreted by EC during liver fibrosis (27,(35)(36)(37)42). Indeed, exosomes contained FN, as detected by FN immunogold labeling (Fig.…”
Section: Fn-integrin Interactions Contribute To Exosome Adhesion and mentioning
confidence: 87%
See 1 more Smart Citation
“…We hypothesized that adhesion between exosomes and HSC may require ligand/receptor interactions to facilitate chemotactic signaling. FN is a glycoprotein of the extracellular matrix that is secreted by EC during liver fibrosis (27,(35)(36)(37)42). Indeed, exosomes contained FN, as detected by FN immunogold labeling (Fig.…”
Section: Fn-integrin Interactions Contribute To Exosome Adhesion and mentioning
confidence: 87%
“…SK1 is an enzyme that produces the HSC chemotactic factor S1P. Additionally, active SK1 enzyme has been detected in the extracellular environment, although not specifically within an exosome fraction (24,25,27,(35)(36)(37). We therefore focused on SK1-derived S1P as a potential pathway relevant to our model of EC-HSC interaction.…”
Section: Sk1 Is An Ec-derived Exosome Protein-becausementioning
confidence: 99%
“…However, there is increasing evidence that the vicious cycle of gut-liver dysfunction can be interrupted by manipulating the gut microbiota. Intestinal decontamination by rifaximin in mice following bile duct ligation reduces liver fibrosis, angiogenesis, and PHT in association with diminished activation of the LPS/TLR4 pathway and fibronectin production, which is limiting the cross talk between HSCs and LSECs [69]. Thus, modulation of the gut-liver axis may prove to be a helpful strategy for preventing and managing NAFLDassociated PHT [70,71].…”
Section: Dysbiosis and The Gut-liver Axismentioning
confidence: 99%
“…Additional agents with impact on HSC activation and contractility include mitochondrial antioxidants [95,96], renin-angiotensin system inhibitors [97], and relaxin [98]. Finally, selective Experimental Intestinal decontamination by rifaximin blocks TLR4-mediated activation of HSCs and modulates FXR signaling by changing intestinal bile acid composition associated with reduced fibrosis, angiogenesis, and PVP in experimental PHT [69] beta3 receptor agonists induce relaxation of HSCs via cAMP accumulation and Rho-kinase inhibition with no effect on normal PVP, indicating that these drugs primarily target the dynamic components of IHVR [99,100]. FXR has recently become a major pharmacological target in NAFLD owing to its complex role in bile acid and lipid metabolism, inflammation, and fibrosis [101].…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Bacterially derived lipopolysaccharides (LPS) bind to their receptor TLR-4 expressed on SEC, inducing injury and inflammation [11]. Interestingly, recent studies have shown that LPS can also induce fibrosis-associated angiogenesis by interacting with TLR-4, highlighting the role of SEC in the so-called gut-liver axis [12,13].…”
Section: Sinusoidal Endothelial Cellsmentioning
confidence: 99%